Conditions for the existence and uniqueness of bounded solutions of nonlinear differential equations - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish conditions required for the existence and uniqueness of bounded solutions of the nonlinear differential equation $f_1\left(\frac{dx(t)}{dt} \right) = f_2(x(t)), t ∈ ℝ$.